AB0988 Effect of Football on Knee Cartilage Thickness: an Ultrasonographic Assessment. (10th June 2014) - Ben Abdelghani, K.; Slouma, M.; Souabni, L.; Kassab, S.; Chekili, S.; Laatar, A.; Zakraoui, L.
Abstract : Background: The effect of physical activity on Knee joint especially the cartilage is unclear. Objectives: The aim of the study was to assess the ultrasonographic thickness measurements of knee cartilage in asymptomatic soccer players (SP) compared to sedentary controls. Methods: A prospective comparative study including 28 males divided into 2 groups: (1) asymptomatic SP recruited from sporting clubs and (2) control group that had never been physically active on a regular basis. Ultrasonography (Esaote MyLab 60 machine and a 13 MHz linear array transducer) was performed on knee joints by a rheumatologist with theoretical and practical training in musculoskeletal ultrasonography and blinded to the identity of subject. With subjects sitting in a comfortable position on the examination table with their knees in maximum flexion, the probe was placed in an axial position on the suprapatellar area. The distal femoral cartilage was visualized as a strongly anechoic structure between the sharp bony cortex and the suprapatellar fat. Three (mid-point) measurements were taken from each knee: the right lateral condyle (RLC), the right intercondylar area (RIA), the right medial condyle (RMC), the left medial condyle (LMC), the left intercondylar area (LIA), and the left lateral condyle (LLC). Both statistical and descriptive analyses were performed. Results: Fifteen SP and 13 healthy controls were enrolled. The mean age was 17±0.55 years in SP group and 17±2.23 years in control group. There were no statistically significant differences between the two groups in age. No history of fracture, surgical intervention or immobilization of the knee was noted in the 2 groups. All SP had practiced sports since the age of 10±1.98 years. The number of hours of training was 10±1 hour weekly. The number of participating to competition was 30.86±7.95 yearly. Matches have been played on synthetic turf soccer fields using soccer shoes with plastic cleats in all cases. Physical examination revealed genu varus in 12 cases in SP group versus 6 cases in control group (p<0.005). No ligament instability was found in all cases. In control group cartilage thickness in different sites was: RIA, RMC, LMC, RLC and LLC were 3.32±0.48 mm, 2.61±0.55 mm, 2.59±0.37 mm, 2.6±0.58 mm and 2.7±0.64 mm respectively. RIA, RMC, LMC, RLC and LLC were 3.72±0.64 mm, 2.68±0.32 mm, 2.84±0.45 mm, 2.83±0.45 mm and 2.89±0.39 mm respectively. The cartilage was thicker in SP group in the three sites (p>0.05). The median cartilage thickness in LIA was 3.2±0.55 mm in the group control versus 3.82±0.57 mm in the SP, the difference was statistically significant (p=0.007) Conclusions: Our study showed that cartilage thickness can be increased in response to sport especially soccer. Thus, physical activity is associated with an increase in cartilage thickness suggesting that soccer can exert a chondroprotective effect when compared to a sedentary lifestyle. Given that optimizing cartilage health is important in preventing osteoarthritis, these findings indicate that physical activity is beneficial to joint. Our study is consistent with previous study showing a positive relationship between physical activity and tibial cartilage volume. References: Donna M. Urquhart, Jephtah F. L. Tobing et al. What is the Effect of Physical Activity on the Knee Joint? Med Sci Sports Exerc. 2011;43(3):432-442. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5362